Analisa Preferensi Wisatawan Domestik Asal Surabaya Dalam Pemilihan Akomodasi Di Bali - Michael Irawan (Tourism Retailing+, 2013)
This study was conducted to determine the preferences and factors of decision making of the domestic tourists from Surabaya in choosing accommodation in Bali. Bali Island is the world's second best island, Boracay Island. The Bali Island is a tourist destination that is recognized by the world, both foreign tourists and domestic travelers. During the tour, travelers need accommodation that suits theirs needs . Preferences and factors that influence the selection of accommodation is different from each one to the other travelers.Analysis techniques used in this study was a descriptive cross tabulations and Spearman Rank Test methods. This methods aims to summarize the information from the original variables and sort into the rank position. The results of this study indicate there are several factors affecting the travelers preferences in choosing a hotel.